Social Networks and Democracy: Problems and Dilemmas of Regulating the Digital Ecosystem - José-ıgnacio Torreblanca (Siyasal: Journal of Political Sciences)
The crisis of representative democracy is to a large extent a crisis of disintermediation. Its best known and most studied manifestation is expressed in the weakening of political parties and representative institutions and the link between them and the citizenry. However, the weakening of traditional media and the progressive replacement of their intermediary role between politics and citizens by social networks, although less studied, is of critical importance. This article analyses how the disintermediation of information facilitated by social networks aggravates the crisis of democracy. It shows how the characteristics of the digital ecosystem facilitate the spread of disinformation and fake news, erode citizens’ trust in the veracity of information and contribute to the undermining of representative democracy and its institutions. It also examines the regulatory strategies being adopted by democratic governments to restore the quality of public space and public confidence in the media and the dilemmas and difficulties they face in doing so.